2005
DOI: 10.5424/srf/2005143-00937
|View full text |Cite
|
Sign up to set email alerts
|

Controlled inoculation of reforestation seedlings with ectomycorrhizal fungi: current knowledge in Spain

Abstract: ResumenDesde el trabajo publicado por Pardos en 1962, se ha desarrollado una importante actividad investigadora en el campo de las ectomicorrizas en España; especialmente en los últimos 20 años. En este artículo, revisaremos los avances conseguidos en el estudio de los hongos ectomicorrícicos en lo que se refiere a su aplicación a la producción de planta para repoblación y a los resultados obtenidos en plantaciones experimentales. Los resultados publicados, principalmente con coníferas inoculadas con hongos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In particular, plants with citrate and tartrate showed a decrease in stem diameter while the addition of malate, oxalate and succinate affected plant cover. Mycorrhizae impose an initial cost on young plants, reducing their performance in the short-term during the early stages of colonization as other studies have found, but this initial cost is compensated by strong benefits later on (Pera & Parladé 2005). This ontogenic transition warrants further investigation in our study system with P. pseudostrobus.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In particular, plants with citrate and tartrate showed a decrease in stem diameter while the addition of malate, oxalate and succinate affected plant cover. Mycorrhizae impose an initial cost on young plants, reducing their performance in the short-term during the early stages of colonization as other studies have found, but this initial cost is compensated by strong benefits later on (Pera & Parladé 2005). This ontogenic transition warrants further investigation in our study system with P. pseudostrobus.…”
Section: Discussionmentioning
confidence: 57%
“…The mutualism between gymnosperms and ectomycorrhizal fungi have been thoroughly studied, and many fungal genera are commonly used to improve gymnosperm growth (Pera & Parladé 2005). Pisolithus arhizus (previously known as Pisolithus tinctorius) is a gasteroid, globose, ectomycorrhiza that has been used with different trees and shrubs to increase their overall growth and root length and volume, as well as phosphorus nutrition, especially in soils with phosphorus deficiency (Gómez-Romero et al 2015, Becerril-Navarrete et al 2022.…”
mentioning
confidence: 99%
“…The candidate relationships between mycorrhiza species and tree species (i.e., study species) used expert-based knowledge and previous studies [23,24]. For the case of ectomycorrhizas, the prepared solution ranged from 5 × 10 5 to 5 × 10 6 spores/mL while for the Rhizophagus spp., a standard inoculation procedure was followed [25].…”
Section: Methodsmentioning
confidence: 99%
“…The fresh weight (g) of each species necessary to inoculate 1,000 seedlings was calculated considering a reference dose of 10 6 active spores, as proved to be the most recommendable to be used with different conifer species and Eucalyptus spp. (Chen et al 2006;Parlade ´et al 1996;Pera and Parlade ´2005;Rinco ´n et al 2007). Calculations considered active spores after 30, 120 and 270 days of storage, with the following formula: necessary fresh weigth ¼ 1 Â 10 6 active spores À Á Â 1; 000 seedlings active spores/g ð Þ…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
“…Mycorrhizal fungi help plants to increase nutrients and water capture, thus improving their establishment and growth, as well as contributing with soil structure restoration and nutrient-cycle re-establishment (Jasper et al 1987). Since these conifers are established on grasslands with no EM species (Fontenla et al 1998), and because altered native forests lose their EM inocula due to degradation, afforestation and restoration activities aim to introduce and/or to re-establish them (Pera and Parlade ´2005;Valenzuela Flores 1993). The simplest and generally more appropriate time to incorporate the EM inocula is during plant production at the nursery.…”
Section: Introductionmentioning
confidence: 99%